Functional Skin Grafts: Where Biomaterials Meet Stem Cells. (1st July 2019) - Kaur, Amtoj; Midha, Swati; Giri, Shibashish; Mohanty, Sujata
Abstract : Skin tissue engineering has attained several clinical milestones making remarkable progress over the past decades. Skin is inhabited by a plethora of cells spatiotemporally arranged in a 3-dimensional (3D) matrix, creating a complex microenvironment of cell-matrix interactions. This complexity makes it difficult to mimic the native skin structure using conventional tissue engineering approaches. With the advent of newer fabrication strategies, the field is evolving rapidly. However, there is still a long way before an artificial skin substitute can fully mimic the functions and anatomical hierarchy of native human skin. The current focus of skin tissue engineers is primarily to develop a 3D construct that maintains the functionality of cultured cells in a guided manner over a period of time. While several natural and synthetic biopolymers have been translated, only partial clinical success is attained so far. Key challenges include the hierarchical complexity of skin anatomy; compositional mismatch in terms of material properties (stiffness, roughness, wettability) and degradation rate; biological complications like varied cell numbers, cell types, matrix gradients in each layer, varied immune responses, and varied methods of fabrication. In addition, with newer biomaterials being adopted for fabricating patient-specific skin substitutes, issues related to escalating processing costs, scalability, and stability of the constructs under in vivo conditions have raised some concerns. This review provides an overview of the field of skin regenerative medicine, existing clinical therapies, and limitations of the current techniques. We have further elaborated on the upcoming tissue engineering strategies that may serve as promising alternatives for generating functional skin substitutes, the pros and cons associated with each technique, and scope of their translational potential in the treatment of chronic skin ailments.